Development of a telescoped synthesis of 4-(1H)-cyanoimidazole core accelerated by orthogonal reaction monitoring. Issue 8 (29th June 2020) - Malig, Thomas C.; Tan, Yichen; Wisniewski, Steven R.; Higman, Carolyn S.; Carrasquillo-Flores, Ronald; Ortiz, Adrian; Purdum, Geoffrey E.; Kolotuchin, Sergei; Hein, Jason E.
Abstract : Telescoped synthesis enabled by reaction monitoring. Abstract : We have developed a convenient two-step, one-pot method for the facile synthesis of cyanoimidazoles. By integrating a suite of reaction-monitoring techniques, we were able to interrogate each transformation independently. We observed that formation of a key hemiaminal intermediate is complicated via many equilibrium processes, creating oligomers and eventually resulting in unproductive dimerization. DoE experiments indicated that despite the complex equilibria of this substrate, high conversion to the trifluoromethyl imidazole can still be achieved. We also report the effects of temperature, pH, and substrate concentrations on the rate and selectivity of the elimination cascade reaction converting the trifluoromethyl imidazole to the cyanoimidazole. By leveraging kinetic information gathered from each step independently, we report reaction conditions to achieve high yields of the cyanoimidazole from carbonyl-containing substrate directly in one pot.